Urban planning instruments at the service of the Environment - Paniagua Marchena, Esteban (Observatorio Medioambiental, 2017)
It is undisputed that big cities are the geographical areas which, due to the better opportunities they offer in terms of employment, as well as education and health services, have a higher population density. These large concentrations of population require more and more goods and services, which implies that the productive activities developed to provide these goods and services, generate important environmental impacts that must be mitigated. In this sense, the real challenge of urbanism, consist in incorporate the sustainable development principles and conservation of natural resources, within the planning of urban spaces, which are currently saturated with noise and pollution. Undoubtedly, the adequate and timely use of urban planning instruments can generate effective tools to control the greater problems on issues as water management, solid waste and urban mobility, making it possible for city dwellers to have more efficient services and a better quality of life.